2016
DOI: 10.2141/jpsa.0150077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flavomycin, <i>Bacillus licheniformis </i>and Enramycin on Performance, Nutrient Digestibility, Gut Morphology and the Intestinal Microflora of Broilers

Abstract: The effects of Flavomycin, Bacillus licheniformis and Enramycin on broiler performance, nutrient digestibility, gut morphology and the intestinal microflora were studied in a 42-d experiment. A total of 288, one-day-old, male, Arbor Acres broilers were randomly assigned to 1 of 4 dietary treatments with 12 pens per treatment and 6 birds per pen. The treatments were comprised of a control diet without supplementation, a diet supplemented with 5 ppm Flavomycin, a diet supplemented with the combination of 5 ppm F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
6
0
3
Order By: Relevance
“…The resistance to Salmonella can be improved by regulating the intestinal bacteria [6]. A large number of previous studies have focused on the therapeutic effect of antibiotics against S. typhimurium infection [15,16]. There has been no such research on the resistance of S. typhimurium through the early construction of different intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance to Salmonella can be improved by regulating the intestinal bacteria [6]. A large number of previous studies have focused on the therapeutic effect of antibiotics against S. typhimurium infection [15,16]. There has been no such research on the resistance of S. typhimurium through the early construction of different intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Flavomycin increases villus length and reduces crypt depth in the duodenum, jejunum and ileum (Ni et al 2012). These combined effects result in reduced weight of intestinal tissue and turnover of mucosal cells (Visek 1978), leading to increased carcass body weight gain (Wang et al 2016;Attia et al 2011). However, antibiotics fed to chickens may cause resistance and cross resistance to antibiotics in pathogenic bacteria (Thapaliya et al 2017), and for E. coli at least, in one study with limited sample size, there was a strong indication that transmission of resistance from poultry to humans had occurred (van den Bogaard et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 showed that the L. plantarum AKK30 culture media with MOS altered the composition of the amino acids, i.e., threonine and isoleucine. For synthesizing amino acids, L. plantarum AKK30 requires MOS to balance the GIT microflora (Rageb et al, 2018) because the amino acid synthesis depended on intestinal microflora conditions such as pH and proteolytic action of endogenous microbial enzymes (Wang et al, 2016). Index of essential amino acid (EAAI) in L. plantarum AKK30 is evidenced that the synbiotic contains amino acids and affect the nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%